KNOWLEDGE AND AWARENESS RELATED TO DIABETES MELLITUS AMONG UNIVERSITY STUDENTS IN SOUTH AFRICA: A CROSS-SECTIONAL STUDY. - Ndlovu, Sanelisiwe Sibusisiwe Vaminhlanhla; Jaya , Ziningi Nobuhle; Thembane, Nokukhanya (Student’s Journal of Health Research Africa, 2025)
Introduction This study assessed diabetes mellitus (DM) knowledge among undergraduate students at a South African University of Technology. Using a cross-sectional, mixed-methods approach, the aim was to compare diabetes knowledge between students in health-related and non-health-related fields, evaluate their attitudes toward diabetes education, and assess self-perceived knowledge. With the rising global prevalence of diabetes, particularly among younger populations, this research explores awareness and education gaps regarding diabetes among university students. Methods The study involved 206 students aged 18-25 from health-related and non-health-related faculties. A pre-validated questionnaire, consisting of multiple-choice, true/false, and open-ended questions, covered diabetes risk factors, symptoms, complications, prevention, and management. Convenience sampling was used, and data was collected through paper-based and electronic surveys. Descriptive statistics summarized the data, while thematic analysis was applied to open-ended responses. Spearman’s correlation assessed the relationship between diabetes knowledge and the field of study. Results Of the participants, 89.2% were aware of diabetes. However, significant knowledge differences were observed between students in health-related and non-health-related fields. Health-related students demonstrated a more accurate understanding of diabetes types, diagnostic methods, and risk factors. In contrast, non-health students showed lower knowledge, with many unable to differentiate between Type 1 and Type 2 diabetes. Correlation analysis revealed a moderate negative relationship (r = -0.352, p < 0.01) between diabetes knowledge and field of study, indicating that non-health students possessed less knowledge. Furthermore, 32.9% of students rated their knowledge as unsatisfactory. Conclusion This study highlights a significant knowledge gap between health-related and non-health-related students. Health-related students showed a more comprehensive understanding, suggesting the need for broader diabetes education for all students across disciplines. Recommendations Diabetes education should be incorporated into university curricula, particularly for non-health students, and public health campaigns should be used to raise awareness.